Caenorhabditis microbiota: worm guts get populated. Issue 1 (December 2016) - Clark, Laura; Hodgkin, Jonathan
Abstract Until recently, almost nothing has been known about the natural microbiota of the model nematodeCaenorhabditis elegans . Reporting their research inBMC Biology, Dirksen and colleagues describe the first sequencing effort to characterize the gut microbiota of environmentally isolatedC. elegans and the related taxaCaenorhabditis briggsae andCaenorhabditis remanei In contrast to the monoxenic, microbiota-free cultures that are studied in hundreds of laboratories, it appears that natural populations ofCaenorhabditis harbor distinct microbiotas.